Laser writing of single-crystalline gold substrates for surface enhanced Raman spectroscopy. (21st July 2017) - Singh, Astha; Sharma, Geeta; Ranjan, Neeraj; Mittholiya, Kshitij; Bhatnagar, Anuj; Singh, B P; Mathur, Deepak; Vasa, Parinda
Abstract: Surface enhanced Raman scattering (SERS) spectroscopy, a powerful contemporary tool for studying low-concentration analytes via surface plasmon induced enhancement of local electric field, is of utility in biochemistry, material science, threat detection, and environmental studies. We have developed a simple, fast, scalable, and relatively low-cost optical method of fabricating and characterizing large-area, reusable and broadband SERS substrates with long storage lifetime. We use tightly focused, intense infra-red laser pulses to write gratings on single-crystalline, Au (1 1 1) gold films on mica which act as SERS substrates. Our single-crystalline SERS substrates compare favourably, in terms of surface quality and roughness, to those fabricated in poly-crystalline Au films. Tests show that our SERS substrates have the potential of detecting urea and 1, 10-phenantroline adulterants in milk and water, respectively, at 0.01 ppm (or lower) concentrations.